Meta-subject research in Polish pedagogy. Introduction to the subject matter - Magier, Piotr (Forum Pedagogiczne, 2020)
The article is introductory, elementary. Its purpose is problem analysis of selected aspects of the achievements of pedagogy in the field of meta-subject research. It addresses issues related to the genesis of meta-subject research, its definition, typologization, function and criticism.